PENGARUH DESENTRALISASI FISKAL DAN AKUNTABILITAS TERHADAP TINGKAT KORUPSI (Studi Kasus Pada Pemerintah Daerah di Pulau Jawa) - Wildhan Khoeron; Tri Jatmiko Wahyu Prabowo (Diponegoro Journal of Accounting, 2025)
This study aims to analyse partially and simultaneously the effect of fiscal decentralisation variables and various accountability indicators on the level of corruption in local governments in Java.The research method uses multiple linear regression analysis with panel data. Data were collected from 115 local governments in Java during the period 2021-2023. Independent variables include fiscal decentralisation (measured by the value of Transfers to Regions and Village Funds/TKDD), LKPD (Local Government Financial Report) opinion, SAKIP (Government Agency Performance Accountability System) score, and EKPPD (Evaluation of Performance of Local Government Administration) score. The dependent variable is the level of corruption as measured by the SPI (Integrity Assessment Survey) score from the KPK.The regression analysis results show that fiscal decentralisation and various accountability indicators (LKPD opinion, SAKIP score, and EKPPD score) partially and simultaneously have a significant influence on the indication of corruption. This finding indicates that these variables contribute significantly to determining the indication of corruption in local government. Thus, the results confirm the importance of improving local government accountability as one of the measures to suppress corrupt practices in the decentralisation process.